Features of Physical Development of Schoolchildren in the Conditions of Specialized Training - Khorolskaya, Elena N.; Pogrebnyak, Tatyana A.; Sagalaeva, Irina V.; Komarova, Marina N.; Goncharova, Natalya S.; Sopina, Natalya A. (International Journal of Criminology and Sociology, 2022)
The article presents a comparative analysis of physical development of 13-year-olds and cadet basic profile of teaching in urban schools in the parameters of somatometry and visiometry characterizing physical development, functional state, adaptation of the heart and body to current training loads. Coming of puberty is marked by intense growth of the body with heterochronous changes in the proportions and dimensions of its muscular skeletal system and the structure of internal organs. During this period, the role of mechanisms for self-regulation of heart activity and, in general, autonomous regulation of the functions of the cardiovascular system increases. At the initial stage in adolescents the manifestation of tachycardia and cardiac type of self-regulation of blood circulation increases. It is accompanied with deterioration in inotropic function of the myocardium against the background of a pronounced effect of sympatotonia and vagotonia on the systolic function of the myocardium.